Cetacean strandings in Costa Rica (1966-1999) - Rodríguez-Fonseca, Javier; Cubero-Pardo, Priscilla (Universidad de Costa Rica, 2001)
Cetacean strandings in Costa Rica are reported for a period of 33 years, with a total of 35 strandings, 13 species and 247 individuals involved. The vast majority of documented strandings occurred on the Pacific coast and correspond to single individuals (32 and 28 strandings respectively). The highest stranding number was in the period from 1990 to 1999 (n=24). Physeter catodon (cachalot or sperm whale) is the species with the highest frequency of strandings (n=8) and the family Delphinidae has the majority of species (n=8) and strandings (n=22). No other general tendencies were determined with the existing data Se informan los casos de encallamientos de cetáceos en Costa Rica. Un total de 35 casos conocidos para 13 especies involucradas y un total de 247 individuos. La gran mayoría de los casos provienen de la costa Pacífica (32) y 28 corresponden a encallamientos individuales. El cachalote, Physeter catodon, es la especie con mayor frecuencia de encallamientos (8) y la familia Delphinidae abarca la mayor cantidad de especies involucradas (8) y de casos de encallamientos (22). No se determinó ninguna otra tendencia general con la información disponible